Estimation of carrying capacity - Ouled Belgacem, Azaiez (International Center for Agricultural Research in the Dry Areas, 2024)
The presentation focuses on the estimation of carrying capacity in silvopastoral systems, emphasizing its critical role in sustainable land management. A key method discussed is the use of integrated assessments to determine the optimal number of livestock that can be supported without degrading the ecosystem. This presentation, delivered by Dr. Azaiez Ouled Belgacem during the group training course on 'Mapping and Inventorying Semi-Arid Silvopastoral Systems,' was held at the ICARDA office in Tunis from May 7 to 10, 2024. The insights shared highlight the importance of balancing livestock production with ecological health to enhance overall ecosystem services.